Geomorphological and geophysical analyses of the Hebron Fault, SW Namibia: implications for stable continental region seismic hazard. Issue 1 (22nd November 2021) - Salomon, G W; New, T; Muir, R A; Whitehead, B; Scheiber-Enslin, S; Smit, J; Stevens, V; Kahle, B; Kahle, R; Eckardt, F D; Alastair Sloan, R
SUMMARY: This study explores the geomorphological expression and geological context of a normal fault scarp in a stable continental region (SCR) which we interpret as having failed in large ( M w >7) earthquakes. Records of such large normal faulting events in an SCR (or even in more rapidly deforming regions) are extremely rare, and so understanding this feature is of international interest. The scarp is exceptionally well-preserved due to the extensive calcrete/silcrete cementation. In areas where this cementation is reduced or absent the scarp is more diffuse, as expected for a feature formed by one or more paleoearthquakes. The exceptional preservation aids comparison with data sets based on scarps which have formed more recently. Our analysis is based on a high-resolution digital elevation model of the Hebron Fault scarp in southern Namibia using pan-sharpened Worldview-3 satellite stereophotos (0.31 m resolution). We make scarp height measurements at 160 locations providing improved estimates of the average displacement (5.9 m), maximum displacement (10.1 m), and the minimum fault length (45 km). No consistent evidence of lateral displacements in water courses or alluvial fan margins were found implying predominantly normal displacement. A newly described section in the northwest has en-echelon scarps consistent with a component of strike-slip motion that may be explained by its difference in strike from the central section. Most channels crossing the fault show a single knick-point. The displacement varies smoothly as it crosses a number of different generations of alluvial fan surfaces. No evidence of a multiscarp or a composite scarp were observed. We have therefore found no evidence for a mutiple-event origin for the scarp, although, this lack of evidence does not conclusively demonstrate a single-event origin. Published regressions, based on the limited data available for SCRs, suggest that the mean expected average displacement (D_av ) for a faults of this length is 1.2–3.1 m implying that the scarp is likely to have formed in 2–5 events with an expected Mw = ∼7.1 though displacements in individual events may exceed these average values. Comparison with the regional geology and aeromagnetic data sets suggests that the fault reactivates a Mesoproterozoic ductile structure, the Nam Shear Zone, and that the location, orientation and segmentation of the scarp is controlled by the alignment of pre-existing structurally weak zones with the present-day stress regime. The fault has undergone repeated brittle reactivation, accumulating ∼110 m of vertical offset since the deposition of the Ediacaran-to-Cambrian Nama Group. This is less than expected from global compilations of total displacement and fault length data, suggesting that the fault rapidly attained its current length by recruiting an existing weak zone and is expected to accumulate displacement at a relatively constant length in the future.